Avaliação da atitude do estudante de medicina da UniversidadeFederal de Minas Gerais, a respeito da relação médico-paciente, nodecorrer do curso médico - Maria Monica Freitas Ribeiro (2006)
The doctor-patient relationship is fundamental to medical care and affects patients psychological, social and biological outcomes. Patient-centered care is an important aspect of the doctor-patient relationship and it takes into account patients preferences, concerns andemotions. Its importance has been recognized by many educators, who emphasize the need for teaching communication skills, humanistic attitudes and behaviors, and ethical and professional values to medical students. The objectives of this study were to examine theattitudes of medical students towards the doctor-patient relationship at medical school of Universidade Federal de Minas Gerais, to describe and quantify the change in these attitudes among students in different years of medical school and to identify factors associated withpatient or doctor-centered attitudes. The Patient-Practitioner Orientation Scale (PPOS), a previously validated instrument used to measure individuals attitudes toward doctor-patient relationship was translated into Portuguese and a socio-demographic questionnaire wascreated. These two instruments were used to survey approximately 800 students in the first, fifth, seventh, ninth, tenth and twelfth semesters of medical school. A total of 738 students (>90%) completed data collection. For the entire cohort, female gender (p=0.000), later semester in medical school (p=0.000), primary-care specialty choice (p=0.013) and lowerfamilial income (p=0.018) were significantly associated with more patient-centered attitudes. Among first semester students only female gender was associated with more patient-centered attitudes. Sharing sub-scores (focusing on power and control) were significantly more patientcentered for twelfth semester male students than for first semester males (p=0.000), but not for female students (p=0.157). Caring sub-scores (focusing on the value of warmth and support) did not change with the years of school. The small increase in patient-centered attitudes among male students and lack of change among female students needs the attention of medical educators and administrators. These results can stimulate the assessment of students attitudes toward the doctor-patient relationship at other Brazilian medical schools, and it would be possible to identify the association between patient-centeredness and thefocus of different curricula. Communication skills need to be taught and the provision of patient care needs to be critically examined by teachers and students aiming to change attitudes toward the doctor-patient relationship to be more patient-centered attitudes.